Machine learning with SAS Viya (SAS Institute Inc., 2020)
Master machine learning with SAS Viya! Machine learning can feel intimidating for new practitioners. Machine Learning with SAS Viya provides everything you need to know to get started with machine learning in SAS Viya, including decision trees, neural networks, and support vector machines. The analytics life cycle is covered from data preparation and discovery to deployment. Working with open-source code? Machine Learning with SAS Viya has you covered - step-by-step instructions are given on how to use SAS Model Manager tools with open source. SAS Model Studio features are highlighted to show.
Based on the SAS training course Machine Learning Using SAS Viya, developed by Carlos Pinheiro, Andy Ravenna, Sharad Saxena, Jeff Thompson, Marya Ilgen-Lieth, and Cat Truxillo. - Includes bibliographical references
Keywords: SAS (Computer file); Machine learning; Computer algorithms; Algorithms; Machine Learning; Apprentissage automatique; Algorithmes; algorithms